Biogeography of global drylands - Maestre, Fernando T.; Benito, Blas M.; Berdugo, Miguel; Concostrina-Zubiri, Laura; Delgado-Baquerizo, Manuel; Eldridge, David J.; Guirado, Emilio; Gross, Nicolas; Kéfi, Sonia; Le Bagousse-Pinguet, Yoann; Ochoa-Hueso, Raúl; Soliveres, Santiago (The New phytologist, 2021)
Despite their extent and socio-ecological importance, a comprehensive biogeographical synthesis of drylands is lacking. Here we synthesize the biogeography of key organisms (vascular and nonvascular vegetation and soil microorganisms), attributes (functional traits, spatial patterns, plant–plant and plant–soil interactions) and processes (productivity and land cover) across global drylands. These areas have a long evolutionary history, are centers of diversification for many plant lineages and include important plant diversity hotspots. This diversity captures a strikingly high portion of the variation in leaf functional diversity observed globally. Part of this functional diversity is associated with the large variation in response and effect traits in the shrubs encroaching dryland grasslands. Aridity and its interplay with the traits of interacting plant species largely shape biogeographical patterns in plant–plant and plant–soil interactions, and in plant spatial patterns. Aridity also drives the composition of biocrust communities and vegetation productivity, which shows large geographical variation. We finish our review by discussing major research gaps, which include: studying regular vegetation spatial patterns; establishing large-scale plant and biocrust field surveys assessing individual-level trait measurements; knowing whether the impacts of plant–plant and plant–soil interactions on biodiversity are predictable; and assessing how elevated CO₂ modulates future aridity conditions and plant productivity.